An investigation on the characteristics of and influence factors for NO2 formation in diesel/methanol dual fuel engine. (1st January 2019) - Lu, Han; Yao, Anren; Yao, Chunde; Chen, Chao; Wang, Bin
Highlights: The existence of methanol premixed region is the main cause of increased NO2 emission in DMDF mode. The impact of temperature on the NO2 emission mainly lies on that of temperature on the NO and HO2 radicals. As the increase of MSP, NO2 emission increases firstly and then decreases. EGR can reduce the NO2 emission, while slightly increased exhaust backpressure can lead to the increase of NO2 . Abstract: It had been found in previous experimental studies that the compression ignition engine with Diesel/Methanol Compound Combustion (DMCC) could significantly increase nitrogen dioxide (NO2 ) emission, compared with conventional diesel mode. However, the detailed formation process and influence factors of NO2 in Diesel/Methanol Dual Fuel (DMDF) engine have not been reported previously. In order to investigate the mechanism of increased NO2 and effect factors of NO2 emission, following works were conducted: Firstly, in light of the literature researches, a hypothesis concerning the NO2 formation procession in DMDF engine was presented, whose demonstration was realized by using numerical simulation; Secondly, the experiments about the effect of methanol substitute proportion (MSP), exhaust gas recirculation (EGR) and exhaust backpressure on the NO2 emission were conducted, whose results were analyzed by using the proved hypothesis. The results of simulation justified that compared with diesel case, the existence of methanol premixed region in DMDF mode was the main cause of increased NO2, and the impact of temperature on the NO2 emission mainly lay in that of temperature on hydroperoxyl (HO2 ) radicals. The experiments showed that along with the increase of MSP, NO2 emission increased firstly and then decreases. The addition of EGR could lead to the reduction of NO2, while the slight increase of exhaust backpressure would increase total nitrogen oxides (NOX ) emission.